Influence of cutting parameters on cutting force and cutting temperature during pocketing operations - Hamidon, R.; Adesta, Erry Yulian Triblas; Riza, Muhammad; Suprianto, Mohammad Yuhan (Asian Research Publishing Network (ARPN), 2016)
Determining of the effect of cutting parameters on cutting force and cutting temperature is particularly important during machining operation. This is because these machining conditions influence the surface quality of machined parts as well as tool life of the cutter. Numerous studies have been conducted to investigate the effect of cutting parameters on machining output. However, most of the studies focussed on straight cutting only. In mould and die making process, end milling process is required to form an empty volume of the part. This is known as pocketing operation. Different from normal cutting, the tool needs to travel in various straight and corner cutting following a particular tool path strategy depending on the shape of the pocket. The situation causes variation in the cutting force as well as cutting temperature due to variation of tool engagement during the process. Hence, this study concentrates on investigating the effects of cutting parameters on cutting forces and cutting temperatures when employing contour tool path strategy for pocket operation. Two different shapes of pocket was employed in this study. The result indicates that Taguchi method is suitable to determine the significant factor in pocketing operation of contour tool path strategy.